Erosion behavior of tungsten coatings in magnetron type discharges with hot cathode - Glazunov, G.P.; Bondarenko, M.N.; Konotopskiy, A.L.; Volkov, E.D. (Вопросы атомной науки и техники, 2008)
The investigations of erosion behavior of vacuum-arc deposited and chemical vapor deposited W-coatings were carried out under steady state plasma impact in magnetron type discharges of cylindrical configuration. For comparison the erosion characteristics were measured for dense bulk tungsten, too. It was shown that erosion rate values both for vacuum-arc deposited and chemical vapor deposited W-coatings are near to that for dense bulk tungsten. The measured erosion rate dependence on atomic number is in good agreement with the data calculated from the equation for mass dependence of physical ion sputtering. Проведені дослідження ерозійної поведінки покриттів вольфраму, осаджених вакуумно-дуговим і газофазним способом, при дії стаціонарної плазми розрядів магнетронного типу циліндрової конфігурації. Для порівняння зміряні також ерозійні характеристики масивного вольфраму. Показано, що величини швидкості ерозії для вакуумно-дугових і газофазних покриттів близькі до таких для щільного масивного вольфраму. Зміряна залежність швидкості ерозії від атомного номера іонів знаходиться в хорошій згоді з розрахунковою по рівнянню для залежності фізичного розпилювання металу від маси іонів. Проведены исследования эрозионного поведения покрытий вольфрама, осажденных вакуумно-дуговым и газофазным способом, при воздействии стационарной плазмы разрядов магнетронного типа цилиндрической конфигурации. Для сравнения измерены также эрозионные характеристики массивного вольфрама. Показано, что величины скорости эрозии для вакуумно-дуговых и газофазных покрытий близки к таковым для плотного массивного вольфрама. Измеренная зависимость скорости эрозии от атомного номера ионов находится в хорошем согласии с расcчитанной по уравнению для зависимости физического распыления металла от массы ионов.